2016
DOI: 10.15405/epsbs.2016.08.99
|View full text |Cite
|
Sign up to set email alerts
|

Linking Person-Job Fit To Employees’ Retention: The Mediating Role of Work Engagement

Abstract: Retaining employees has become an important issue for the companies because retention helps the organizations to achieve their goals. This study intends to identify factors used to increase employees' retention. Specifically, this study examines the relationship between person-job (PJ) fit, work engagement (WE), and employees' retention. The study also determines the role of WE as a plausible mediating variable between PJ fit and employees' retention. The study was conducted among 268 engineers in semiconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Studies have shown that adaptability between the individual and job has a direct effect on all aspects of work-related stress. In this regard, nurses who are psychologically empowered are able to efficiently manage work-related stress (Deniz et al, 2015;Özbas & Tel, 2016). On the other hand, nurses who do not have the ability to achieve a balance in their emotional relationship with patients and have no control over their interpersonal relationships experience a higher level of work-related stress (Saifan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that adaptability between the individual and job has a direct effect on all aspects of work-related stress. In this regard, nurses who are psychologically empowered are able to efficiently manage work-related stress (Deniz et al, 2015;Özbas & Tel, 2016). On the other hand, nurses who do not have the ability to achieve a balance in their emotional relationship with patients and have no control over their interpersonal relationships experience a higher level of work-related stress (Saifan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(2014) state that, should there be a balance between individual skill and task difficulty, the employee engages with their work more deeply, and declares that time flies while working. Additionally, it is among the findings of the literature that employees with a high degree of fit with their job are more absorbed in their work (Bui et al., 2017; Enwereuzor et al., 2018; Hamid & Yahya, 2016). Especially for those individuals who feel effective and successful in their jobs, having high degrees of KSAs play a role in job absorption (Lu et al., 2014).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…A high level of P-J fit positively contributes to job satisfaction/motivation level, job performance, employee retention, work engagement, and employee well-being (Edwards, 1991;Lee, Kim, 2020;Wu et al, www.orgpsyjournal.hse.ru 2020). Employees with high P-J fit are more confident in executing their new ideas (John, Hin, 2015) and performing their jobs with lesser number of mistakes (Hamid, Yahya, 2016) because of the necessary knowledge, skills, and abilities for completing the jobs (June et al, 2013). Moreover, when there is a good match between a person and a job, the training efficiency is higher and the trainees will become higher-valued assets for an organization (Bhat, Rainayee, 2016).…”
Section: Introductionmentioning
confidence: 99%